MODERNIZATION'S DOPPELGÄNGER. (16th October 2015) - MANDLER, PETER
Abstract : Modernization theory has rightly become a central topic of twentieth-century US intellectual history. Not only does it represent a key movement in modern economics, but modernization theory's purposeful interdisciplinarity ropes in psychology, sociology and political science (at least), and makes it stand as one of the main pillars of the new interdiscipline of behavioral science that was so influential in the postwar Western academy. As an equally purposeful policy science, modernization theory also played an important role in a raft of postwar political initiatives—in the Cold War, in international economic development, in the organization of science, in counterinsurgency and the Vietnam War. This unusually fruitful (albeit often unusually destructive) intermeshing of ideas and politics has been neatly exemplified in the person of Walt Rostow, "America's Rasputin, " who parlayed a politically unpromising track record as an economic historian into a role as one of the principal strategists of the Vietnam War. Opinion differs as to how determinative modernization theory's ideas were; Bruce Kuklick has suggested of most social science in this period that it "served to legitimate but not to energize politics, " or, as a participant put it more trenchantly in 1949, "The administrator uses social science the way a drunk uses a lamppost, for support rather than for illumination." Still, most intellectual historians would be happy (though not necessarily proud) to think that their key concepts provided even support for the major political enterprises of their day.